Polyamide‐6 composites reinforced with cellulose fibers and fabricated by extrusion: Effect of fiber bleaching on mechanical properties and stability. Issue 2 (29th May 2015) - Fernandes, Felipe Cicaroni; Gadioli, Renan; Yassitepe, Emre; De Paoli, Marco‐Aurelio
Abstract : We prepared polyamide‐6 (PA‐6) composites using bleached and semibleached cellulose fibers from Eucalyptus species by processing in a corotating interpenetrating twin‐screw extruder. PA‐6 is a challenging matrix because of its high processing temperature, which overlaps the thermodegradation temperature of the fibers. The selection of the processing conditions for extrusion and the use of the lubricant ethylene bis (stearamide) permitted the production of composites with 20, 30, and 40 wt% of bleached fibers, which are lighter than the corresponding glass fiber composites. Composites with 30 wt% of bleached fibers yield the best mechanical properties and good fiber/matrix interaction, as demonstrated by mechanical tests and scanning electron microscopy. X‐ray photoelectron spectroscopy studies showed that the natural moisture in the fibers promotes the fiber/matrix interaction through the formation of ester bonds. We assessed the effect caused by the presence of lignin in the fibers. Composites containing 30 wt% of semibleached fibers maintained the flexural properties and showed small improvements in thermal stability when compared with bleached fiber composites; however, there is a slight decrease in the tensile properties. Through accelerated aging tests, we observed that increased lignin concentration in the fibers reduced the formation of carbonyl compounds on sample surfaces, indicating a stabilization effect. POLYM. COMPOS., 38:299–308, 2017. © 2015 Society of Plastics Engineers